The Determination of Service Quality, Price, and Customer Satisfaction in Increasing Repurchase Intention in the Mining Sector - Prameswari, Gita; Kurniawan, Daniel (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the influence of service quality, price, and customer satisfaction on repurchase intention in the mining sector. With rising competition, mining companies face the challenge of customer retention through enhanced service quality, competitive pricing, and customer satisfaction. Using a quantitative approach, surveys were distributed to customers from various mining companies, and multiple regression analysis was used to evaluate the relationships between these variables. The results show that service quality and price significantly impact customer satisfaction, positively influencing repurchase intention. Furthermore, customer satisfaction acts as a mediating variable, strengthening the relationship between service quality, price, and repurchase intention. These findings offer practical insights for mining companies in formulating strategies focused on service quality and pricing to increase customer loyalty.